Performance of sustainable alkali activated mortars containing solid waste ceramic powder - Huseien, G.; Ismail, Mohamed; Tahir, M.; Mirza, J.; Hussein, A.; Khalid, N.; Sarbini, N. (The Italian Association of Chemical Engineering, 2018)
As the cement industry contributed to increasing the global carbon dioxide emissions, researchers looked for other sustainable alternatives. Among them, one of the alternatives is alkali activated mortar containing no cement at all. Alkali-activated mortar is manufactured using industrial and agricultural wastes like ceramics, palm-oil fuel ash (POFA), granulated blast furnace slag (GBFS), fly ash (FA), metakaolin (MK), etc. Compared with Ordinary Portland Cement (OPC), alkali-activated is considered as a highly environmental product based mortar. The alkali activated mortar feasibility production using ceramic waste binder was evaluated in this study. The effect of replacing GBFS binder by ceramic powder (by varying percentage) upon its fresh-state properties, like workability, setting time, density and hardened properties such as compressive, tensile and flexural strengths of alkali-activated mortar was concurrently examined. The impact of curing regime on strength development of ceramic-GBFS based alkali activated was evaluated as well. Results revealed that with increased ceramic to GBFS content, the workability and setting time of mortar improved whereas the density decreased. On the other hand, when ceramic was replaced by up to 50 % of GBFS, it showed higher strengths as compared to OPC mortar. It is concluded that alkali activated mortar incorporating 100 percent wastes could be used in the construction industry with the almost negligible amount of environmental problems.